Media Use Learning Audio Visual In Efforts To Increase Student Learning Achievement - Syelly Eka Permatasari (Jurnal Scientia, 2023)
This research aims to: (1) Find out the implementation of Audio Visual Learning media in an effort to increase student motivation and (2) Find out the implementation of Audio Visual Learning media in an effort to increase student learning achievement in BI subjects at YB Vocational School . The subjects of this research were class XI students. This type of research is included in PTK (Classroom Action Research). Observations were carried out to measure the implementation of BI learning using Audio Visual Learning media. Written tests are carried out to measure learning and student achievement. Questionnaires were given to determine student responses. As for data analysis techniques For instrument sheet observation And sheet questionnaire using formula percentage, For instrument Test questions use the percentage formula. Research result shows that applicability instructional Media Audio Visuals in BI learning can increase student motivation and learning achievement. This is based on the average percentage of student learning achievement in cycle I of 67.21 and the average student achievement in cycle II of 71.73. Apart from that, students gave a very positive response to the application of Audio Visual Learning media in BI learning . This is based on the percentage of questionnaire results of 95.65% of students responding very positively and 4.35% of students responding positively.